Nivel de conocimientos y su relación con el Cumplimiento de las normas de bioseguridad en el Personal que labora en centro obstétrico del Hospital II- 2 tarapoto. Enero – Diciembre 2014 - Becerra Mirano, María Elita (2014)
This study entitled "Level of knowledge and its relation to the compliance of Biosafety personnel working in the Obstetric Hospital Center Tarapoto II 2 , January-December 2014 " , aimed to : determine the relationship between The level of knowledge and compliance with biosafety regulations in the staff Working in the Obstetric Hospital Center II - 2 Tarapoto Descriptive, Quantitative , prospective, correlational study whose instrument was the Questionnaire , the sample consisted of 42 health personnel working in Obstetrics . The results were the study population was characterized by the study Population was characterized as primarily the age group of 46-50 years with 26 % (11), with a working time in the institution of 6-10 years 29 % (12 ) and A labor time in the service delivery ward 6 to 10 years with 33 % (14 ) . The Level of knowledge about biosafety standards of health personnel working at The Obstetric Center , Hospital II - 2 Tarapoto, is regular with 95 % (40) . The Level of compliance with biosafety standards for personnel working in the Obstetric Center Hospital II - 2 Tarapoto , is regularly adequate with 50% ( 21) for both cases , there difference between occupational group for Professionals 76 % (32 ) and 24% (10 ) in nursing technicians . In conclusion if there is significant relationship between the level of Awareness and compliance with the rules on biosafety staff working in Obstetric center in the Hospital II - 2 Tarapoto, chi 2 = 2.1 ( p < 0.1).